A Ship Cargo Hold Inspection Approach Using Laser Vision Systems - MI Chao; LIU Haiwei; ZHAO Ning; SHEN Yang (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
Our paper represents a vision system based on the laser measurement system (LMS) for bulk ship inspection. The LMS scanner with 2-axis servo system is installed on the ship loader to build the shape of the ship. Then, a group of real-time image processing algorithms are implemented to compute the shape of the cargo hold, the inclination angle of the ship and the relative position between the ship loader and the cargo hold. Based on those computed inspection data of the ship, the ship loader can accomplish the bulk cargo loading operation automatically. Finally, our paper describes and analyzes the experiment of the Laser Vision System in Coal Terminal of Tianjin Port. DOI: http://dx.doi.org/10.11591/telkomnika.v11i1.1904